A correlation of ineffective erythropoiesis and dysregulated signaling pathways in myelodysplastic syndromes/neoplasms - Junying Wu; Jinqin Liu; Jia Chen; Lin Yang; Fuhui Li; Tiejun Qin; Zefeng Xu; Jing Liu; Jiaxi Zhou; Lihong Shi; Bing Li; Zhijian Xiao (Experimental Hematology & Oncology)
Abstract Over 90% of patients with myelodysplastic syndromes/neoplasms (MDS) exhibit anemia at diagnosis, primarily due to ineffective erythropoiesis. This is characterized by abnormal proliferation and differentiation of erythroid cells influenced by signaling pathways including heme synthesis, ferroptosis, senescence and apoptosis. Despite widespread anemia, the specific mechanisms and pathway alterations at different disease stages are not well understood. This study employed the NUP98-HOXD13 (NHD13) transgenic mouse model, which mimicked the erythroid changes observed in MDS patients, to explore these dynamic pathway changes during disease progression. Based on the severity of anemia and changes in mean corpuscular volume (MCV), four time points were selected: 6 weeks (non-anemic), 12 weeks (mild anemia), 16 weeks (obvious anemia) and 20 weeks (severe macrocytic anemia). The findings indicated that a reduction in erythroid-committed progenitors and impaired erythroid maturation were linked to ineffective erythropoiesis. As the disease progressed, signaling pathways dynamically changed. Heme metabolism and ferroptosis pathways were significantly upregulated in the pre-disease and early disease stages, while senescence and cell cycle pathways were activated in the early stage. The prominent roles of apoptosis, pyroptosis and inflammasome signaling pathways were observed in the late stage. Notably, changes in Gpx4 and Ncoa4 expression, along with transmission electron microscopy analysis, suggested that ferroptosis played a critical role in the early stage of the disease. To our knowledge, this is the first report of the signaling pathway dynamics associated with ineffective erythropoiesis during the pathogenesis and progression of MDS, highlighting potential targets for therapeutic intervention at various stages of the disease.